2013
DOI: 10.1038/mp.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutation in the dopamine transporter gene associates dopamine dysfunction with autism spectrum disorder

Abstract: De novo genetic variation is an important class of risk factors for autism spectrum disorder (ASD). Recently, whole exome sequencing of ASD families has identified a novel de novo missense mutation in the human dopamine (DA) transporter (hDAT) gene, which results in a Thr to Met substitution at site 356 (hDAT T356M). The dopamine transporter (DAT) is a presynaptic membrane protein that regulates dopaminergic tone in the central nervous system by mediating the high-affinity re-uptake of synaptically released DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
239
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(261 citation statements)
references
References 82 publications
(91 reference statements)
12
239
0
1
Order By: Relevance
“…Some evidence suggests that DA is involved in mediating some of the same maternal behaviours that are exhibited under the influence of OXT 93,94 as well as pair bonding. [95][96][97][98] Furthermore, OXT has been implicated in helping to mediate addiction and withdrawal in the mesolimbic dopaminergic pathways, 99 and differences in peripheral and central levels of OXT have been found in patients with disorders with potential DA abnormalities, such as autism, [100][101][102][103] schizophrenia [104][105][106][107][108] and social anxiety disorder. [109][110][111][112] In addition, preclinical studies have shown that dopaminergic fibres may regulate OXT release 113,114 and that the receptor binding sites and neuronal fibres of both of these neurochemicals reside in the same regions of the central nervous system and are often next to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that DA is involved in mediating some of the same maternal behaviours that are exhibited under the influence of OXT 93,94 as well as pair bonding. [95][96][97][98] Furthermore, OXT has been implicated in helping to mediate addiction and withdrawal in the mesolimbic dopaminergic pathways, 99 and differences in peripheral and central levels of OXT have been found in patients with disorders with potential DA abnormalities, such as autism, [100][101][102][103] schizophrenia [104][105][106][107][108] and social anxiety disorder. [109][110][111][112] In addition, preclinical studies have shown that dopaminergic fibres may regulate OXT release 113,114 and that the receptor binding sites and neuronal fibres of both of these neurochemicals reside in the same regions of the central nervous system and are often next to each other.…”
Section: Discussionmentioning
confidence: 99%
“…We present here, on the basis of the crystal structure from Drosophila melanogaster dopamine transporter (dDAT) (PDB ID: 4XP1) (Wang et al, 2015), a molecular model of 5-MAPB bound to rat DAT (rDAT), in comparison with that of dopamine, amphetamine, 5-APB, MDMA, cocaine and RTI-121 also bound to rDAT. Our studies compare the structural changes produced by various ligands binding to rDAT to the already ongoing work in hDAT models (Hamilton et al, 2013;Hansen et al, 2014;Khelashvili et al, 2015aKhelashvili et al, , 2015b since it is the primary animal model used in functional studies and pre-clinical drug abuse testing.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The construction of the homology model of rDAT (rDAT dDAT ) in complex with dopamine uses established protocols previously described for the construction of a human DAT (hDAT) model (Hamilton et al, 2013;Hansen et al, 2014;Khelashvili et al, 2015aKhelashvili et al, , 2015b. Briefly, as the template, the homology model uses the recent crystal structure of the neurotransmitter sodium symporter (NSS) DAT from Drosophila melanogaster (dDAT) bound to dopamine (PDB ID: 4XP1) (Wang et al, 2015).…”
Section: Fcv Data Analysismentioning
confidence: 99%
“…One possibility is that increased demand for melanin in the skin depletes the supply of tyrosine for dopamine synthesis. Genetic mutations in dopamine transport proteins have been linked to autism [195,196]. The defect features a persistent reverse transport of dopamine (substrate efflux from the synapse), which reduces the amount of time extracellular dopamine is available for signalling effects [195].…”
Section: Cataracts and Melanomamentioning
confidence: 99%
“…Genetic mutations in dopamine transport proteins have been linked to autism [195,196]. The defect features a persistent reverse transport of dopamine (substrate efflux from the synapse), which reduces the amount of time extracellular dopamine is available for signalling effects [195]. Other genes of the dopaminergic network are also linked to autism, including syntaxin [197] and enzymes involved in dopamine metabolism [198].…”
Section: Cataracts and Melanomamentioning
confidence: 99%